Effective Network Formation of PEDOT by in-situ Polymerization Using Novel Organic Template and Nanocomposite Supercapacitor. (1st September 2017) - Zhou, Huanyu; Liu, Gengling; Liu, Jinliang; Wang, Yilin; Ai, Qingyun; Huang, Jun; Yuan, Zhongyi; Tan, Licheng; Chen, Yiwang
Graphical abstract: Highlights: The novel π conjugated sulfonate is utilized to polymerize PEDOT as template. Crystalline and conductive PEDOT with quinoid-conformation and effective network is developed. The continuous interpenetrating network is further formed by auxiliary π-π interaction of MWCNT. The nanocomposites are demonstrated for owning potential applications in supercapacitors. Abstract: Different π-conjugated sulfonate templates, including dodecylbenzenesulfonate (DBS), 2-naphthalenesulfonate (NAS), N, N'-bis(2, 6-diisopropylphenyl)-perylenediimide-1, 6, 7, 12-tetraoxyphenylsulfonate (PTS), as well as auxiliary assistance by graphene (Gra) and multi-walled carbon nanotube (MWCNT), have been utilized to investigate the polymerization behavior of 3, 4-ethylenedioxythiophene (EDOT) and the influence on the corresponding morphologies and properties. PEDOT has been self-polymerized with obviously agglomeration without template. Isolated PEDOT grains with coiled shape have been formed by DBS template polymerization. More crystalline and conductive PEDOT with quinoid-conformation and ordered arrangement has been developed by utilizing template with novel π conjugated sulfonate (PTS). Most prominently, the obtained conductive PEDOT:MWCNT shows continuous interpenetrating network structure with more extended PEDOT and well-dispersed MWCNT due to π-π interaction of PEDOT with noncovalent functionalized MWCNT by electron-deficient conjugated sulfonate. Furthermore, a high specific capacitance of 199 F g −1 at current density of 0.5 A g −1 for PEDOT:MWCNT has also been demonstrated successfully for owning potential applications in supercapacitors.